1996
DOI: 10.33584/jnzg.1996.58.2227
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of caucasian clover based pastures under irrigation

Abstract: Grasslands Kara cocksfoot, Grasslands Nui ryegrass, Grasslands Roa tall fescue, Grasslands Gala grazing brome and Grasslands Maru phalaris were sown as single grass species with either white or Caucasian clover during December 1993, on a Lismore stony silt loam in Canterbury. Plots were irrigated and rotationally grazed by sheep. Total herbage produced during the first measurement period (September 1994 to July 1995) averaged 13.6 t DM/ha. All white clover-based swards produced similar yields, but with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 8 publications
0
17
2
Order By: Relevance
“…At the three sites in Minnesota, WC production was, however, more than twofold greater than KC in 12 of 18 site–herbicide–N treatment combinations. Others have also reported greater first‐year production of WC when compared with KC (Spencer et al, 1975; Moss et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…At the three sites in Minnesota, WC production was, however, more than twofold greater than KC in 12 of 18 site–herbicide–N treatment combinations. Others have also reported greater first‐year production of WC when compared with KC (Spencer et al, 1975; Moss et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…In New Zealand, associations of WC with different grasses had higher legume content (40%) than associations of these same grasses with KC (15%) 10 months after seeding. However, after 28 months, KC occupied a greater percentage of the sward (17%) than WC (5%) (Moss et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…The similar number of grazing days (Table 4) and pre‐grazing herbage mass (Table 5), measured for both clover species, was in contrast with Moss et al. (1996).…”
Section: Discussionmentioning
confidence: 77%
“…Irrigation is normally practised in the Canterbury region of New Zealand to finish lambs using permanent pastures, while sheep farms without irrigation are also common in the region. Previous studies in Canterbury have reported greater DM yields by Caucasian clover compared with white clover in swards both with irrigation (Moss et al. , 1996) and without irrigation (Black et al.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation